2015
DOI: 10.1007/s10120-015-0577-x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporters 1, 3, 6, and 10 are expressed in gastric cancer and glucose transporter 3 is associated with UICC stage and survival

Abstract: Background Due to proliferation and increased metabolism, cancer cells have high glucose requirements. The glucose uptake of cells is influenced by a group of membrane proteins denoted the glucose transporter family (Glut-1 to -12). Whereas increased expression and a negative correlation with survival have been described for Glut-1 in several types of cancer, the impact of other glucose transporters on tumor biology is widely unknown. Methods In this retrospective study, gastric cancer specimens of 150 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 32 publications
3
50
2
Order By: Relevance
“…GLUT1 and glycolytic enzymes associated with catabolizing glucose are transcriptionally regulated by HIF1A and MYC oncogenes such as HIF1A and MYC, which are activated in cancers with increased GLUT1 expression. GLUT3 expression has also been associated with poor prognosis in various cancers . However, we did not detect a compensatory upregulation of GLUT3 expression in ESCC cells after inhibiting GLUT1.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…GLUT1 and glycolytic enzymes associated with catabolizing glucose are transcriptionally regulated by HIF1A and MYC oncogenes such as HIF1A and MYC, which are activated in cancers with increased GLUT1 expression. GLUT3 expression has also been associated with poor prognosis in various cancers . However, we did not detect a compensatory upregulation of GLUT3 expression in ESCC cells after inhibiting GLUT1.…”
Section: Discussioncontrasting
confidence: 82%
“…GLUT3 expression has also been associated with poor prognosis in various cancers. 23 However, we did not detect a compensatory upregulation of GLUT3 expression in ESCC cells after inhibiting GLUT1. In contrast, HK2, which catalyzes the conversion of glucose to glucose-6-phosphate, was upregulated in GLUT1silenced cells.…”
Section: Discussioncontrasting
confidence: 62%
“…All of the included studies measured the expression of GLUT1 by means of immunohistochemistry (IHC) staining or PCR in human tissues, and the cut-off values varied across studies. Among the studies, 4 evaluated lung cancer [58], 3 evaluated pancreatic cancer [911], 3 evaluated breast cancer [12, 14], 2 evaluated gallbladder cancer [10, 15], 2 evaluated gastric cancer [16, 17], 2 evaluated colorectal cancer [18, 19], 2 evaluated laryngeal cancer [20, 21], and 1 each evaluated hypopharyngeal cancer [22], endometrial cancer [23], salivary gland tumor [24], adrenocortical cancer [25], liver cancer [26], ampulla of Vater cancer [10], extrahepatic bile duct cancer [10], oral cancer [27], neuroblastic tumors [28], cervical cancer [29], ovarian cancer [30] and esophageal cancer [31]. Due to the retrospective design of the included studies, only five studies examined both OS and DFS [6, 12, 14, 25, 29].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies indicated that there was a poor prognostic value of GLUT1 in oral squamous cell carcinoma [27], malignant salivary gland tumors [24], colorectal cancer [18, 19], gastric cancer [16, 17], gallbladder cancer [10, 15], extrahepatic bile duct cancer [10], adrenocortical carcinoma [25] and neuroblastic tumor [28]. Others studies found there was no significant association between GLUT1 expression with prognosis in laryngeal cancer [20, 21], ampulla of vater cancer [10], extrahepatic bile duct cancer [10], cervical cancer [29], and ovarian cancer [2].…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies indicate that appropriate patient selection can lead to a significant improvement of the accuracy of using FDG-PET-CT for lymph node assessment (27,28). For such patient selection, it seems beneficial to include extra features such as GLUT-1 expression; this glucose transporter molecule is important in gastric cancer glucose metabolism (37)(38)(39). Other tracers used for PET did not demonstrate reproducible benefits for determining staging so far.…”
Section: Discussionmentioning
confidence: 99%